PENGARUH KOMPETENSI, MOTIVASI, DAN KOMITMEN ORGANISASI PADA KINERJA MANAJERIAL BANK PERKREDITAN RAKYAT SEKABUPATEN GIANYAR - Hita Wasana, Jero Komang; Ary Wirajaya, I Gde (E-Jurnal Akuntansi, 2015)
Performance is the result of both the quality and quantity of work produced in accordance manager responsibilities given. Competition banking and financial institutions implies the need to optimize the performance of managers in the BPR that still exist. In other words, to improve competitiveness, the various factors that increase the performance manager needs serious attention. This study aims to determine the effect of competence, motivation, and commitment to the organization's managerial performance BPR Gianyar regency. The sample used a total of 33 BPR with 99 respondents. The sample is determined by the method of sampling nonprobability sampelajenuh. Dataayang analysis technique used is multiple linear regression. Results of testing the hypothesis in mind that competence, motivation and organizational commitment have positive influence on managerial performance BPR Gianyar regency.
Keywords: competence, motivation, organizational commitment, and managerial performance